2023
DOI: 10.1093/g3journal/jkad121
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific estimation of cis and trans regulation of gene expression in heads and gonads of Drosophila melanogaster

Abstract: The regulatory architecture of gene expression is known to differ substantially between sexes in Drosophila, but most studies performed so far used whole-body data and only single crosses, which may have limited their scope to detect patterns that are robust across tissues and biological replicates. Here, we use allele-specific gene expression of parental and reciprocal hybrid crosses between 6 Drosophila melanogaster inbred lines to quantify cis- and trans-regulatory variation in heads and gonads of both sexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 63 publications
2
12
1
Order By: Relevance
“…These values are considerably higher than the values (6-17%) reported by Puixeu et al (2023). The greater divergence of haplotypes used in our study may have contributed to this difference; we crossed fly lines from different continents whereas they crossed lines from within a single population.…”
Section: Discussioncontrasting
confidence: 77%
See 4 more Smart Citations
“…These values are considerably higher than the values (6-17%) reported by Puixeu et al (2023). The greater divergence of haplotypes used in our study may have contributed to this difference; we crossed fly lines from different continents whereas they crossed lines from within a single population.…”
Section: Discussioncontrasting
confidence: 77%
“…Based on population genetic analyses of human and fly data, Cheng & Kirkpatrick (2016) concluded that sexual conflict is the most intense in moderately sex-biased genes; this may lead one to predict cisregulatory variation being most common in genes with an intermediate sex bias. Two previous studies of cis-regulatory variation in D. melanogaster found different patterns from one another and neither matched this prediction (Osada et al 2017;Puixeu et al 2023).…”
mentioning
confidence: 57%
See 3 more Smart Citations